Parasitism by Tylenchid Nematodes in Natural Populations of Pintomyia fischeri (Diptera: Psychodidae: Phlebotominae) in Argentina - Villarquide, Maria Lucrecia (2020)
Fil: Villarquide, Maria Lucrecia. Instituto Universitario de Ciencias de la Salud. Fundación Barceló; Argentina.